The effects of thermal swimsuit on thermoregulatory responses during water exercise - Wakabayashi, H.; Sugano, A.; Nomura, T. (Biomechanics and Medicine in Swimming IX, 2003)
The purpose of this study was to evaluate the effects of a thermal swimsuit (TS) on thermoregulatory responses of male subjects during water immersion at rest and water exercise. Five healthy male subjects performed two types of experiment (TS and nonnal swimsuit; SS). They sat at room temperature (5 min), immersed at rest in the water (29.1 'C, 10 min), performed water exercise (RPE 11-13, lOmin), and sat at room temperature (10 min). Esophagus temperature (T •• ), skin temperatures (Tsk), rating of thermal sensation (RTS), 0 2 consumption (V02), respiratory exchange ratio (RER), heart rate (HR) and rating of perceived exertion (RPE) were measured during the experiments. Metabolic heat production (M) was calculated from V02 and RER. And total (tissue and swimsuit) insulation was derived from Tes, Tsk, water temperature and M. RTS was higher in TS, however no difference was found between TS and SS in the mean values of body temperature and insulation. Although higher RTS was observed, there were no significant effects of TS on body temperatures (T b) and insulation during water immersion at rest and water exercise at the T w of 29.1 'C for 20 min immersion time in healthy males.